2021
DOI: 10.1017/s1366728921000298
|View full text |Cite
|
Sign up to set email alerts
|

How (not) to cross a boundary: Crosslinguistic influence in simultaneous bilingual children's event construal

Abstract: Simultaneous bilingual children sometimes display crosslinguistic influence (CLI), widely attested in the domain of morphosyntax. It remains less clear whether CLI affects bilinguals’ event construal, what motivates its occurrence and directionality, and how developmentally persistent it is. The present study tested predictions generated by the structural overlap hypothesis and the co-activation account in the motion event domain. 96 English–French bilingual children of two age groups and 96 age-matched monoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 58 publications
1
26
2
Order By: Relevance
“…Motion event typology has served as an extremely useful framework for examining bilingual cognition and language use. Two issues that have been at the heart of much research is whether and to what extent bilinguals develop language-specific patterns of thinking-for-speaking and the role of CLI (e.g., Hohenstein et al, 2006 ; Daller et al, 2011 ; Engemann et al, 2012 ; Aveledo and Athanasopoulos, 2016 ; Engemann, 2016 , 2021 ; Miller et al, 2018 ; Wang and Wei, 2021 ). The studies have mostly focused on typologically contrasting languages (English vs. French/Spanish) and have involved both child and adult bilinguals.…”
Section: Motion Event Expressions In Bilingualismmentioning
confidence: 99%
See 2 more Smart Citations
“…Motion event typology has served as an extremely useful framework for examining bilingual cognition and language use. Two issues that have been at the heart of much research is whether and to what extent bilinguals develop language-specific patterns of thinking-for-speaking and the role of CLI (e.g., Hohenstein et al, 2006 ; Daller et al, 2011 ; Engemann et al, 2012 ; Aveledo and Athanasopoulos, 2016 ; Engemann, 2016 , 2021 ; Miller et al, 2018 ; Wang and Wei, 2021 ). The studies have mostly focused on typologically contrasting languages (English vs. French/Spanish) and have involved both child and adult bilinguals.…”
Section: Motion Event Expressions In Bilingualismmentioning
confidence: 99%
“… Serratrice, 2016 ), a couple of extant studies indicate that CLI may increase over time (cf. Aveledo and Athanasopoulos, 2016 ; Engemann, 2021 ).…”
Section: Motion Event Expressions In Bilingualismmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the quadrilingual children in this study differ from monolingual children learning v-languages who tend to focus on path rather than manner (Hickmann, 2006;Hickmann et al, 2018). They do, however, align with successive and simultaneous bilingual children acquiring s-and v-languages who extensively use manner verbs and path satellites in v-languages (Akta-Erciyes, 2020;Engemann, 2016Engemann, , 2021Nicoladis & Brisard, 2002).…”
Section: Discussionmentioning
confidence: 59%
“…In a recent study, Engemann (2021) found that French-English simultaneous bilingual children-living in France and reportedly exposed to equal input in both languages from birth-maintained the typological patterns of each of their languages, mainly combining manner verbs with path satellites in English but using fewer satellites in French. Engemann (2021) also found examples of crosslinguistic influence, showing that the children used more path verbs in their English compared to English monolinguals, whereas they in French used manner verbs and path satellites more frequently than French monolinguals.…”
Section: Previous Researchmentioning
confidence: 98%